From Media Hype to Twitter Storm The Dynamics of Self Reinforcing Processes in News Waves - Vasterman, Peter (Amsterdam University Press, 2018)
The word media hype is often used as rhetorical argument to dismiss waves of media attention as overblown, disproportional and exaggerated. But these explosive news waves, as well as - nowadays - the twitter storms, are object of scientific research, because they are an important phenomenon in the public area. Sometimes it is indeed 'much ado about nothing' but in many cases these media storms have play an important role in political issues, scandals and crises. Twitter storms sometimes ruin reputations within hours. Although different concepts are used, such as media hypes, news waves, media storms, information cascades or risk amplification, all the studies in this book refer to the same process in which key events trigger a chain of reactions and interactions, building up huge news waves in the media or rapidly spreading social epidemics in the social media.